Emprego dos monofilamentos de Semmens Weinstein e termografia na avaliação da sensibilidade em pacientes diabéticos tipo 2 com risco para neuropatia periférica diabética - Mendes, Giorgia Caroline (2019)
Diabetes Miellitus is a non-transmissible chronic disease currently regarded as a Public Health matter, and which derives from the lack of Insulin and/or the Insulin's incapacity to carry out its functions properly. The Diabetic Feet is one of the most common complications associated with the Diabetes Mellitus and which occurs over the disease progression time. Such a diabetic neuropathy tends to be progressive and affects more aggressively patients with poorer glycemic control. Clinical examination includes both obtaining a thorough clinical record, as well as detailed exams of the feet by using the Semmens Weinstein monofilaments to determine lesser-sensible areas on the feet. The resulting imagery is used for diagnostics; however the said resource does not demonstrate the presence of pain, but vasomotor changes instead. The aim of the study was to compare the techniques of the use of the Semmens Weinstein Monofilaments and Thermographic Imagery in the assessment of sensibility on Diabetes 2 patients incurring the risk of diabetic peripheral neuropathy, by carrying out the lower limbs thermal mapping; assessing the tactile sensibility of pre-selected individuals through the use of the Semmens Weinstein Monofilaments and correlating their temperature readings with the tactile sensibility. It is as a transversal, qualitative and quantitative study with a population of 30 individuals with DM type 2. The two assessment techniques used favored the diagnosis and a more assertive prognosis to DM patients, thus making possible an early diagnostic, along with a better clinical evolution of the disease hence lowering the high costs for Public Health and improving the quality of life of DM patients.